Estimation of the salivary levels of monocyte chemoattractant protein-1 and macrophage inflammatory protein-1α in periodontitis patients with and without diabetes in comparison to systemically and periodontally healthy individuals - Sahithi Sunkara; Sandhya Pavankumar; Trinath Kishore Damera; Durga Bhavani Kundrapu (Journal of Indian Society of Periodontology, 2025)
Background: Early identification of periodontal disease, mainly in diabetic patients, is crucial for the prognosis and treatment planning. Biochemical signaling during periodontal disease involves the production of cytokines. Chemokines belong to the group of chemotactic cytokines that are able to activate and migrate a variety of cells, like bone cells and leukocytes, which stimulate inflammatory events. Chemotactic chemokines, monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein-1 alpha (MIP-1α) are secreted by different types of cells. These salivary biomarkers might be of use in assessing periodontal disease presence, risk and progression, especially in diabetic patients. Materials and Methods: Thirteen milliliters of unstimulated whole saliva were collected from five groups: Systemically and periodontally healthy individuals, gingivitis patients without diabetes, periodontitis patients without diabetes, periodontitis patients with diabetes, and periodontally healthy diabetic individuals. The samples were then centrifuged at 2600 rpm for 15 min at 4°C, and the supernatant was kept at − 80°C until additional analysis. The enzyme-linked immunosorbent assay was used to examine the amounts of MCP-1 and MIP-1α in the saliva. Results: Levels of MCP-1 and MIP-1α were significantly higher in periodontitis with diabetes group (P = 0.000) than in other groups. Receiver operating curve showed 95% specificity and 100% sensitivity for MCP-1 and MIP-1α, respectively, in detecting periodontitis, especially in diabetic individuals.” Conclusion: The present study illustrates that salivary biomarkers MCP-1 and MIP-1α might be promising biomarkers in differentiating periodontal disease from health, especially in diabetic individuals.